Sources of particulate-matter air pollution and its oxidative potential in Europe - Daellenbach, Kaspar R.; Uzu, Gaëlle; Jiang, Jianhui; Cassagnes, Laure-Estelle; Leni, Zaira; Vlachou, Athanasia; Stefenelli, Giulia; Canonaco, Francesco; Weber, Samuël; Segers, Arjo; Kuenen, Jeroen J. P.; Schaap, Martijn; et al. (Nature (London), 2020)
Particulate matter is a component of ambient air pollution that has been linked to millions of annual premature deaths globally 1 – 3 . Assessments of the chronic and acute effects of particulate matter on human health tend to be based on mass concentration, with particle size and composition also thought to play a part 4 . Oxidative potential has been suggested to be one of the many possible drivers of the acute health effects of particulate matter, but the link remains uncertain 5 – 8 . Studies investigating the particulate-matter components that manifest an oxidative activity have yielded conflicting results 7 . In consequence, there is still much to be learned about the sources of particulate matter that may control the oxidative potential concentration 7 . Here we use field observations and air-quality modelling to quantify the major primary and secondary sources of particulate matter and of oxidative potential in Europe. We find that secondary inorganic components, crustal material and secondary biogenic organic aerosols control the mass concentration of particulate matter. By contrast, oxidative potential concentration is associated mostly with anthropogenic sources, in particular with fine-mode secondary organic aerosols largely from residential biomass burning and coarse-mode metals from vehicular non-exhaust emissions. Our results suggest that mitigation strategies aimed at reducing the mass concentrations of particulate matter alone may not reduce the oxidative potential concentration. If the oxidative potential can be linked to major health impacts, it may be more effective to control specific sources of particulate matter rather than overall particulate mass. Observations and air-quality modelling reveal that the sources of particulate matter and oxidative potential in Europe are different, implying that reducing mass concentrations of particulate matter alone may not reduce oxidative potential.